Psychiatric Pharmaceuticals as Emerging Contaminants in Wastewater - Silva, Bruna; Costa, Filomena; Neves, Isabel C.; Tavares, Teresa (SpringerBriefs in Green Chemistry for Sustainability,, 2015)
This book describes how psychiatric pharmaceuticals, namely antidepressants, anxiolytics, sedatives and hypnotics are among the most prescribed active substances due to the higher occurrence of psychiatric disorders throughout the world. It goes on to demonstrate how patients' excretion of the active compounds along with several metabolites is considered to be the main pathway for the occurrence of these emerging pollutants in wastewater treatment plant effluents, surface and drinking water, soils and sediments. Further chapters are devoted to an exploration of these pharmaceuticals' high persistence, toxicity and intrinsic biological activity, which can affect the nervous and endocrine systems of terrestrial and aquatic non-target organisms, the dissemination of these compounds in environment matrices and the growing number of associated problems and concerns. The remainder of the book describes how conventional wastewater treatment processes are generally inefficient when it comes to the removal of this type of pollutants, giving rise to the demand for implementing alternative or complementary treatment technologies. Extensive research studies on the efficiency of the degradation and/or removal of these pollutants are summarized, and adsorption, membrane and advanced oxidation processes (AOP) are proposed. Given its content and structure, the book offers a concise summary of the most significant findings on psychiatric pharmaceutical removal in wastewater.